Respuesta :
(a) 4.0 m/s
We can solve this part just by analyzing the vertical motion of the froghopper.
The initial vertical velocity of the froghopper as it jumps from the ground is given by
[tex]u_y = u_0 sin \theta[/tex] (1)
where
[tex]u_0[/tex] is the takeoff speed
[tex]\theta=58.0^{\circ}[/tex] is the angle of takeoff
The maximum height reached by the froghopper is
h = 58.7 cm = 0.587 m
We know that at the point of maximum height, the vertical velocity is zero:
[tex]v_y = 0[/tex]
Since the vertical motion is an accelerated motion with constant (de)celeration [tex]g=-9.8 m/s^2[/tex], we can use the following SUVAT equation:
[tex]v_y^2 - u_y^2 = 2gh[/tex]
Solving for [tex]u_y[/tex],
[tex]u_y = \sqrt{v_y^2-2gh}=\sqrt{-2(-9.8)(0.587)}=3.4 m/s[/tex]
And using eq.(1), we can now find the initial takeoff speed:
[tex]u_0 = \frac{u_y}{sin \theta}=\frac{3.4}{sin 58.0^{\circ}}=4.0 m/s[/tex]
(b) 1.47 m
For this part, we have to analyze the horizontal motion of the froghopper.
The horizontal velocity of the froghopper is
[tex]u_x = u_0 cos \theta = (4.0) cos 58.0^{\circ} =2.1 m/s[/tex]
And this horizontal velocity is constant during the entire motion.
We now have to calculate the time the froghopper takes to reach the ground: this is equal to twice the time it takes to reach the maximum height.
The time needed to reach the maximum height can be found through the equation
[tex]v_y = u_y + gt[/tex]
Solving for t,
[tex]t=-\frac{u_y}{g}=-\frac{3.4}{9.8}=0.35 s[/tex]
So the time the froghopper takes to reach the ground is
[tex]T=2t=2(0.35)=0.70 s[/tex]
And since the horizontal motion is a uniform motion, we can now find the horizontal distance covered:
[tex]d=u_x T = (2.1)(0.70)=1.47 m[/tex]